Development of a pill based on the essential oil of Lippia alba (Research, Society and Development, 2020)
The lemongrass (Lippia alba quimiotipo II; Verbenaceae), a plant species that is part of the list of medicinal plants of the program Live Pharmacy of Ceará, has in its leaves essential oil rich in citral, which accounts for its anxiolytic property. The accomplishment of the present research will aim at the implementation of a new pharmaceutical form based on lemongrass in “Farmácias Vivas” that can be used for the treatment of anxiety. This oil will be obtained by hydrodistillation method. The base of the tablet will consist of lactose, cellulose, alcohol, 10% starch solution and L. alba essential oil. The granulate was evaluated by the apparent density, compacted density, Hausner Ratio, Carr Index, resting angle, flow velocity, organoleptic property and humidity. The obtained mixture presents adequate flowability according to the analysis parameters. The tablet was evaluated by weight average, hardness, friability, disintegration and thin layer chromatography.